Block Copolymer Synthesis by a Sequential Addition Strategy from the Organocatalytic Group Transfer Polymerization of Methyl Methacrylate to the Ring‐Opening Polymerization of Lactide. Issue 20 (2nd August 2022) - Zaky, Mohamed Samir; Guichard, Gilles; Taton, Daniel
Abstract: Sequential block copolymerization involving comonomers belonging to different classes, e.g., a vinyl‐type monomer and a heterocycle, is a challenging task in macromolecular chemistry, as corresponding propagating species do not interconvert easily from one to the other by crossover reactions. Here, it is first evidenced that 1‐methoxy 2‐methyl 1‐trimethylsilyloxypropene (MTS), i.e., a silyl ketene acetal (SKA)‐containing initiator, can be used in presence of the P4 ‐ t ‐Bu phosphazene organic base to control the ring‐opening polymerization (ROP) of racemic lactide ( rac ‐LA). The elementary reaction, which rapidly transforms SKA groups into propagating alkoxides, can be leveraged to directly synthesize well‐defined poly(methyl methacrylate)‐ b ‐polylactide block copolymers. This is achieved using P4 ‐ t ‐Bu as the single organic catalyst and MTS as the initiator for the group transfer polymerization of methyl methacrylate, followed by the ROP of rac ‐LA. Both polymerization methods are implemented under selective and controlled/living conditions at room temperature in THF. This sequential addition strategy further expands the scope of organic catalysis of polymerizations for macromolecular engineering of block copolymers involving propagating species of disparate reactivity. Abstract : The P4 ‐ t ‐Bu Brønsted organic base is here employed to directly switch from the group transfer polymerization of methyl methacrylate to the ring‐opening polymerization of lactide, allowing an easy access to well‐defined poly(methyl methacrylate)‐b‐polylactide block copolymers by an organocatalytic pathway.